Исследование сил резания при фрезеровании цветных металлов - Розенберг А. М. Александр Минеевич; Куфарев Г. Л. Георгий Леонидович; Розенберг Ю. А. Юрий Александрович; Козлов А. А.; Тахман А. А. (1965, 1965)
Заглавие с титульного листа